Kembali ke Kasus: Menghidupkan Kembali Tradisi Laporan Kasus Untuk Menjembatani Praktik dan Konsep Dalam Psikologi - Yulianto, Jony Eko; Abraham, Juneman; Siaputra, Ide Bagus (Faculty of Psychology, Universitas Surabaya, 2026)
This editorial invites Psychology practitioners, scientists, and researchers to re-embrace case reports as a legitimate and meaningful scientific medium for bridging professional practice and conceptual development. Case reports possess the power to capture the complexity of human experience in a contextual and reflective manner—a characteristic that is increasingly relevant amidst limited time, resources, and the demands of real-world practice. Through historical and interdisciplinary review, this editorial emphasizes that case reports are not a marginal form of writing, but rather a scholarly contribution capable of enriching theory, practice, and academic dialogue. Based on this, ANIMA Indonesian Psychological Journal is opening a case report submission category with editorial and peer-review standards equivalent to those for other articles. This initiative aims to provide an inclusive space for authors from various backgrounds and career stages—both novice and experienced—to reflect on Psychology practice ethically, contextually, and with quality.